?ANION EXCHANGE STUDIES ON HYDROUS ZIRCONIUM OXIDE IN PARTIALLY NON- AQUEOUS SOLVENT SYSTEM (Biological Sciences - PJSIR, 1995)
The anionexchangebehaviourofthetransitionelements,chromium,manganese,ironandcobalt wasstudiedover hydrous zirconium oxide (HZO) driedat 35°Cusingethanol/methanol-water mixture containing hydrochloric acid as solvent system. The distribution coefficient (K) in ethanol-hydrochloric acid system is found to be higher than that observed inmethanol-hydrochloricacidsystem.TheselectivityorderinbothsystemsisCr(lII»Fe(lI)~Co(II»Mn(Il). Successful column separation of metal ions has beencarried out using such mixtures of suitable composition.